2020
DOI: 10.1101/2020.05.14.20101998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity and COVID-19: The role of visceral adipose tissue

Abstract: INTRODUCTION: During the unprecedented health crisis of the COVID-19 pandemic it was suggested that obesity might aggravate severe acute respiratory syndrome coronavirus-2 (SARS CoV-2). Therefore, this study aims to investigate the association between Compute Tomography (CT)-based measurements of visceral and subcutaneous fat as measures of obesity and COVID-19 severity. METHODS: 30 patients with laboratory-confirmed COVID-19 and a mean age of 65.59 plus/minus 13.06 years from a level one medical center i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Lastly, the cross-sectional nature of the BIA measurements complicates inter-individual comparability. As both disease and treatment influence body composition, mainly through loss of LBM and increase of fluid overload, differences in time-to-measurement are an important consideration [ 45 , 46 ]. In particular, for ICU patients, in whom fluid overload is common and has prevented BIA measurements from becoming a standard of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the cross-sectional nature of the BIA measurements complicates inter-individual comparability. As both disease and treatment influence body composition, mainly through loss of LBM and increase of fluid overload, differences in time-to-measurement are an important consideration [ 45 , 46 ]. In particular, for ICU patients, in whom fluid overload is common and has prevented BIA measurements from becoming a standard of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Simonnet et al [ 46 ] identified a risk factor for severity in COVID-19 patients that was solely dependent on the BMI value. Nevertheless, Petersen et al [ 52 ] indicated that visceral adipose tissue and upper abdominal circumference directly raise the risk of COVID-19 incidence and proposed the use of CT-based visceral adipose tissue quantification as a specific risk assessment tool for SARS-CoV-2 patients on regularly obtained chest CTs. Certain factors that exacerbate the clinical evolution of COVID-19 infection in obese patients are the difficulty of pulmonary ventilation in these subjects, with reduced diaphragmatic excursions and a remarkable increase in anatomical death space [ 12 ].…”
Section: Obesity and Covid-19mentioning
confidence: 99%
“…During the health crisis due to the COVID-19 pandemic, multiple studies suggested that obesity could exacerbate the acute respiratory syndrome. In a study by Petersen et al [20] that included 30 patients confirmed for COVID-19 by qPCR from a medical center in Berlin, Germany, retrospectively analyzed, hospitalized in an ICU, and under mechanical ventilation, an increase in visceral fat per square decimeter, as well as each additional centimeter of abdominal circumference, was associated with an increased risk of requiring mechanical ventilation in a hospitalized patient. This is in line with the results of this survey as demonstrated with the Pearson test.…”
Section: Discussionmentioning
confidence: 99%